Memetakan Strategi Kepemimpinan Pastoral di Era Posmodern - Munatar Kause; Daud Darmadi (Jurnal Teologi Gracia Deo, 2020)
This study aims to show the characteristics and views of the truth that is held by the community and the church in the postmodern era. The second objective is to find a model of pastoral care that is relevant for congregations who have been affected by postmodern culture. The method used is literature research by comparing, synthesizing, and analyzing various literature related to pastoral care in the postmodern era. The results of the literature study presented in this study indicate that the influence of postmodern views has entered the life of the congregation, which views that the truth of the Word of God is no longer absolute, but they create views of truth that are subjectively created. Pastoral leadership services to deal with this are, 1) Leaders must be spiritual 2) Leaders must have vision 3) Leaders must change.In addition, the model of pastoral care to the congregation that can be done is 1) Conducting training for lay people, 2) Creating cell groups 3) Doing personal service.